At the Limits of Cultural Heritage Rights? The Glasgow Bajuni Campaign and the UK Immigration System: A Case Study. Issue 1 (19th March 2018) - Hill, Emma C.; Craith, Máiréad Nic; Clopot, Cristina
Abstract: In 2003, the Convention for the Safeguarding of Intangible Cultural Heritage (UNESCO ICH Convention) formalized provision for forms of heritage not solely rooted in the material world. This expanded the scope and accessibility of cultural heritage rights for communities and groups. To much commentary and critique, the United Kingdom (UK) infamously decided not to ratify the UNESCO ICH Convention. This article examines the implications of the UK's decision not to ratify the Convention for the cultural heritage and human rights of an asylum-seeking group in Glasgow, Scotland, namely, the Glasgow Bajuni campaigners, members of a minority Somali clan. Based on participatory ethnographic fieldwork with the group and analysis of their asylum cases, this article makes two observations: first, that the UK's absence from the Convention establishes a precedent in which other state actors (that is, immigration authorities) are emboldened to advance skepticism over matters involving intangible cultural heritage and, second, that despite this, limitations in current provisions in the UNESCO ICH Convention would provide the group with little additional protection than they currently have. Developing these observations, we critique current UK approaches to intangible cultural heritage as complicit in the maintenance of hierarchies and the border. Finally, we consider the extent to which the current provisions of the UNESCO ICH Convention might be improved to include migrant and asylum-seeking groups.